Modelling users, context and devices for adaptive user interface systems. Issue 1 (2014) - ,; ,; ,
Abstract : Purpose – The purpose of this paper is to review the state‐of‐the‐art in adaptive user interface systems by studying their historical development over the past 20 years. Moreover, this paper contributes with a specific model combining three main entities (users, context and devices) that have been demonstrated to be always represented in these environments. Novel concepts that should be taken into account in these systems are also presented.Design/methodology/approach – The authors first provide a review and a comparison of current user interface adaptive systems. Next, the authors detail the most significant models and the set of techniques used to, finally, propose a novel model based on the studied literature.Findings – Literature solutions for adaptive user interface systems tend to be very domain dependant. This situation restricts the possibility of sharing and exporting the information between such systems. Furthermore, the studied approaches barely highlight the dynamism of these models.Originality/value – The paper is a review of adaptive user interface systems and models. Although there are several reviews in this area, there is a lack of research for modelling users, context and devices simultaneously in this domain. The paper also presents several significant concepts that should be taken into account to bring an adaptive and dynamic perspective to the studied models. Acknowledgements : This work has been supported by project grants "UCADAMI: User and Context‐aware Dynamically Adaptable Mobile Interfaces" (S‐PE12FD006) and "DYNUI: Capability and Context‐aware Dynamic Adaptation of User Interfaces for Ambient Assisted Living" (PC2012‐73A), sponsored by the Basque Government's Industry and Education Departments, respectively.